PENGEMBANGAN INSTRUMEN PENILAIAN TES DIAGNOSTIK PILIHAN GANDA DUA TINGKAT UNTUK MENGUKUR HASIL BELAJAR SISWA MATERI HIDROKARBON DI SMA 10 NEGERI PONTIANAK - Deska Dewati; Dini Hadiarti; Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACT In general, the used evaluation form to measure the students’ abilities is evaluation form in multiple choice and essay, but this evaluation still has weaknesses which are there are possibilities that the students do not know the correct answer and it has low realibility. From the weaknesses, the researcher wanted to produce two levels multiple choice diagnostic test assessment instrument in order to find outthe passing of the students’ outcomes with 21 students for the first trial and 118 students for the main trial. This research consisted of 7 steps which were (1) Research and the collection of information, (2) Planning, (3) The development of introductory product, (4) Preliminary trial, (5) The revision on main product, (6) Field trial, and (7) The revision of product. The research result showed that the two levels multiple choice diagnostic test was feasible to be used. The test result from 118 students using the two levels multiple choice diagnostic test showed the validity value of Vainstrument was 3.97, the effectiveness value was 85.57 %, and the practical value was 78.80%. The obtained test result, before and after using the two levels multiple choice diagnostic test showed that there was improvement on students’ learning outcomes which was 59.3 %. Therefore, the two levels multiple choice diagnostic test can measure and improve the students’ learning outcomes.Keywords: Development, Two Levels Multiple Choice, Two Levels Multiple Choice DiagnosticTest